Risk Management Committee, Company Complexity, Public Accounting Firm Size and Audit Fees - Agil Novriansa; Asfeni Nurullah; Aryanto Aryanto; Muhammad Akbar Prayoga Putra; Dela Mutia (Faculty of Economics, Universitas Sriwijaya, 2022)
This study aims to empirically examine the relationship between the risk management committee, company complexity, and public accounting (PA) firm size and audit fees. This study uses panel data with a span of 9 years of observation. The sample for this research is a non-financial company registered on the Indonesian capital market in 2012-2020. The results of purposive sampling showed that the number of samples in this study was 414 firm-year observations. The results of panel data regression analysis with the fixed effect model and clustered standard error show that risk management committee and PA firm size are positively related to audit fees, while company complexity is not related to audit fees. An important implication of the results of this research is that it is important for companies to have a risk management committee that stands alone in order to improve the corporate governance process.